2016
DOI: 10.1038/nature17959
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 promotes heart repair by activating the antioxidant response after cardiac injury

Abstract: Summary Myocardial infarction results in compromised myocardial function with heart failure due to insufficient cardiomyocyte self-renewal1. Unlike lower vertebrates, mammalian hearts only have a transient neonatal renewal capacity2. Reactivating primitive reparative ability in the mature heart requires knowledge of the mechanisms promoting early heart repair. By testing an established Hippo-deficient heart regeneration model for renewal promoting factors, we found that Pitx2 expression was induced in injured,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
256
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 242 publications
(276 citation statements)
references
References 32 publications
12
256
1
Order By: Relevance
“…In all cases, disruption of the targeted NRF2 gene did not lead to any apparent structural and functional abnormalities in the neonatal and early postnatal heart under non-stressed physiological conditions [79]. However, NRF2 deficiency resulted in a rapid onset of cardiac dysfunction during experimental pressure overload (due to transverse aortic constriction [80]) or regional ischemic injury (due to cardiac artery occlusion [81,82] in young adult (2-month-old) mice. These results indicated that NRF2 inhibition can increase sensitivity of the young heart to pathological stress and thus exaggerate susceptibility to cardiac dysfunction.…”
Section: Nrf2 Transcription Factormentioning
confidence: 94%
See 4 more Smart Citations
“…In all cases, disruption of the targeted NRF2 gene did not lead to any apparent structural and functional abnormalities in the neonatal and early postnatal heart under non-stressed physiological conditions [79]. However, NRF2 deficiency resulted in a rapid onset of cardiac dysfunction during experimental pressure overload (due to transverse aortic constriction [80]) or regional ischemic injury (due to cardiac artery occlusion [81,82] in young adult (2-month-old) mice. These results indicated that NRF2 inhibition can increase sensitivity of the young heart to pathological stress and thus exaggerate susceptibility to cardiac dysfunction.…”
Section: Nrf2 Transcription Factormentioning
confidence: 94%
“…These results indicated that NRF2 inhibition can increase sensitivity of the young heart to pathological stress and thus exaggerate susceptibility to cardiac dysfunction. Recently, it was found that NRF2 loss-of-function leads to suppression and distortion of regenerative processes in the apex resection mouse model [82].…”
Section: Nrf2 Transcription Factormentioning
confidence: 99%
See 3 more Smart Citations